Students’ L2 Motivation Shift in Two-Year Access Microscholarship Program - Khasanah, Wirdatul (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study investigates the changes in English learning motivation among Indonesian university students participating in the US-sponsored English Access Microsholarship program. Using Dornyei’s L2 Motivational Sels system as a framewrok, the research examines students’ motivation before and after the program. Using semi-structured interview as the main data collection, this study found that students joining Access program in Jember experienced motivational changes after 2 years. They shifted from local oriented into more internationally driven motivation to learn English. The findings also found that positive learning experiences and cultural exposures can transform learner’s goals and attitudes.